Effect of carbon and nitrogen sources on the production of lipase by Candida cylindracea 2031 in batch fermentation - I. M., Noor; M., Hasan; K. B., Ramachandran (2006)
Production of extracellular lipase by Candida cylindracea DSMZ 2031 was studied in a seven litres batch bioreactor, using palm oil (PO), palmitic acid (PA), lauric acid (LA), olive oil (OO) and cooking oil (CO) as carbon source. The effect of carbon and nitrogen sources was studied by measuring the lipase activity. The maximum lipase activity was found to be 12.7 kLU on palm oil as carbon source and urea as nitrogen source. This was achieved at a temperature of 30o C, pH of 6.0, agitation speed of 500 rpm and aeration of 1vvm.